METHODS OF POLITICAL PROPAGANDA AND MANIPULATION AND PSYCHOLOGICAL MECHANISMS IN SHAPING PUBLIC OPINION - Shahobjon KUBATOV,; Shahruza AHMADJANOVA, (Ustozlar uchun, 2025)
Abstract: This article explores the methods of political propaganda and manipulation and examines the psychological mechanisms employed in shaping public opinion. By integrating insights from political psychology, communication studies, and cognitive science, the study highlights how political actors influence perceptions, attitudes, and behaviors. The analysis emphasizes both traditional techniques of persuasion and the transformative role of digital media in modern political communication.